High-strength and high-conductivity Cu-Ti-Fe alloy and preparation method thereof
By adding Fe elements to Cu-Ti alloy and performing multi-step process processing, a high-strength and high-conductive Cu-Ti-Fe alloy was prepared, which solved the problems of unstable performance and short service life of Cu-Ti alloy, and achieved the improvement of the high strength and conductivity of the alloy.
Patent Information
- Application Number
- CN202411805981.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-04-04
AI Technical Summary
Cu-Ti alloys have problems of unstable performance and short service life, making it difficult to provide high-strength, high-stability and conductive copper alloy materials.
High-strength and high-conductivity Cu-Ti-Fe alloy was prepared by adding an appropriate amount of Fe elements to the Cu-Ti alloy and adopting the process flow of annealing treatment, hot extrusion, solid solution treatment, cold rolling deformation and aging treatment.
The addition of Fe element inhibits the growth of alloy grains, increases the total area of grain boundaries, increases the hindering effect of dislocations, and thus increases the strength of the alloy. In the aging treatment, Fe elements promote the precipitation of nano-sized Fe2Ti phases and improve the conductivity of the alloy.
Smart Images

Figure CN119753418A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of alloys, and in particular relates to a high-strength and high-conductivity Cu-Ti-Fe alloy and a preparation method thereof. Background Art
[0002] Copper and copper alloys are widely used in electronics, electrical, transportation, communications, national defense and military industries due to their good thermal conductivity, electrical conductivity, corrosion resistance, antibacterial and mechanical properties. High-strength and high-conductivity copper alloys have both good strength and conductivity. They are an important direction in the copper and copper alloy industry and one of the advanced materials that developed countries are competing to develop. As a material with integrated structure and function, high-strength and high-conductivity copper alloys are widely used in integrated circuit lead frames, high-speed rail contact wires, high-voltage switch contacts, strong magnets, resistance spot welding electrodes and electromagnetic gun rails.
[0003] The output and quality of copper processing products directly determine the development of downstream application industries such as electronics, transportation, and national defense. In order to meet the application needs of different fields in industrial production, copper alloy materials have developed many different series and are widely used. Among them, Cu-Ti alloy has attracted widespread attention for its high strength, high elasticity, good welding performance and fatigue resistance, and is regarded as the most likely alloy series to replace Cu-Be alloy. In addition, the study found a simple method to extract Ti elements from the alloy, which will also make the recycling of Cu-Ti alloy simple. Environmentally friendly and excellent performance Cu-Ti alloy (high strength, high elasticity, fatigue resistance) is undoubtedly a better choice. However, Cu-Ti alloy still has the problems of unstable performance and short service life. Therefore, how to provide a copper alloy material with high strength, high stability and conductivity is of great significance to the development of the electronics industry. Summary of the invention
[0004] In order to solve the above technical problems, the present invention proposes a high-strength and high-conductivity Cu-Ti-Fe alloy and a preparation method thereof.
[0005] To achieve the above object, the present invention provides the following technical solutions:
[0006] A method for preparing a high-strength and high-conductivity Cu-Ti-Fe alloy comprises the following steps:
[0007] The iron block and part of the copper block are smelted to obtain a Cu-Fe master alloy, which is then smelted with a titanium block and the remaining copper block to obtain an alloy ingot;
[0008] The alloy ingot is subjected to annealing treatment, hot extrusion, solution treatment, cold rolling deformation and aging treatment in sequence to obtain the high-strength and high-conductivity Cu-Ti-Fe alloy.
[0009] Beneficial effects: The present invention adds an appropriate amount of Fe element on the basis of the existing Cu-Ti alloy. The addition of Fe element can inhibit the growth of dynamic recrystallization grains of the alloy, thereby achieving the purpose of grain refinement, and the total area of grain boundaries is significantly increased. Secondly, the Cu-Ti-Fe alloy is cold-rolled. After cold rolling, the dislocation density in the alloy is increased, which hinders the further slip of dislocations. This hindering effect requires a greater force to make the dislocations cross the grain boundaries when the alloy is subjected to external forces, thereby increasing the strength of the alloy. In addition, grain refinement can also increase the number of dislocation obstacles in copper-titanium alloys. As the grain size decreases, the dislocation density within a single grain decreases, but the grain boundaries serve as obstacles to dislocation movement, and their number increases with the refinement of the grains. This makes it more difficult for dislocations to move and concentrate inside the grains when the alloy is subjected to external forces, thereby avoiding the occurrence of stress concentration, and further improving the strength of the alloy. Finally, the alloy is subjected to aging treatment. During the aging process, the Fe element promotes the precipitation of nano-sized Fe2Ti phase in the alloy, which has a good coherent relationship with the copper matrix and can produce coherent strengthening. At the same time, it reduces the concentration of solute atoms in the matrix, weakens the scattering effect of the copper matrix lattice distortion on electrons, and thus improves the conductivity of the alloy.
[0010] Preferably, the mass ratio of the iron block to part of the copper block is 1:9.
[0011] Preferably, the smelting is carried out under a protective atmosphere, the smelting temperature is 1050-1100° C., the time is 0.5-1 h, and the pressure is 0.05 MPa.
[0012] Beneficial effects: Under the above conditions, the generation of harmful impurities (such as oxides and sulfides) can be reduced, the volatilization of key elements at high temperatures can be effectively controlled, the components can be fully mixed, the uniformity of the chemical composition can be ensured, and the purity and performance of the alloy can be improved.
[0013] Preferably, the annealing treatment is: heating the alloy ingot to 880° C. and keeping the temperature for 40 minutes.
[0014] Beneficial effects: Under the above conditions, the inhomogeneity of alloy structure and composition can be eliminated.
[0015] Preferably, the hot extrusion is: keeping the temperature at 880° C. for 40 minutes, and then hot extruding into rods, with an extrusion ratio of 5 to 10:1.
[0016] Beneficial effects: Under the above conditions, the structure can be effectively refined, shrinkage cavities and shrinkage in the cast structure can be eliminated, the density of the structure can be increased, and the properties of the alloy can be improved.
[0017] Preferably, the solution treatment is: keeping at 920° C. for 1 hour and then quenching in water.
[0018] Beneficial effect: Under the above conditions, the solute atoms can be fully dissolved in the matrix.
[0019] Preferably, the deformation amount of the cold rolling deformation is 60%.
[0020] Beneficial effects: Under the above conditions, the alloy strength can be improved and the precipitation of strengthening phase can be promoted.
[0021] Preferably, the aging treatment is carried out at a temperature of 450-550°C and for a time of 10-480 min.
[0022] More preferably, the aging temperature is 400°C, 450°C, 500°C and 550°C, and the aging time is 10 min, 20 min, 30 min, 60 min, 120 min, 240 min and 480 min.
[0023] Beneficial effects: Under the above conditions, the precipitation of strengthening phase can be promoted and the comprehensive properties of the alloy can be improved.
[0024] A high-strength and high-conductivity Cu-Ti-Fe alloy prepared by the above preparation method.
[0025] Preferably, the following components are included in mass fraction:
[0026] Ti: 1.3-1.6%, Fe: 0.5%, and the balance is Cu and inevitable impurities.
[0027] Beneficial effect: Under the above component ratio, a strengthening phase can be formed to improve the strength and conductivity of the alloy.
[0028] Compared with the prior art, the present invention has the following advantages and technical effects:
[0029] The present invention is to prepare a Cu-Ti-Fe alloy by adding Fe elements. After cold rolling deformation, the dislocation density in the alloy is increased, and a strengthening effect is produced. The addition of Fe elements can inhibit the growth of dynamic recrystallization grains of the alloy, thereby producing a fine grain strengthening effect, and improving the strength and hardness of the alloy. During the aging process, the Fe element promotes the precipitation of nano-sized Fe2Ti phases in the alloy, which have a good coherence relationship with the copper matrix and can produce a coherence strengthening effect. At the same time, the concentration of solute atoms in the matrix is reduced, and the scattering effect of the copper matrix lattice distortion on electrons is weakened, thereby improving the electrical conductivity of the alloy. Therefore, the Cu-Ti-Fe alloy prepared by the present invention has high strength and certain electrical conductivity, and can be widely used in the field of electronic information. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:
[0031] Figure 1 This is a flow chart of the Cu-Ti-Fe alloy obtained in Example 1 of the present invention;
[0032] Figure 2 This is the TEM micrograph of the Cu-Ti-Fe alloy obtained in Example 1 of the present invention. DETAILED DESCRIPTION
[0033] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0034] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.
[0035] The embodiment of the present invention discloses a method for preparing a high-strength and high-conductivity Cu-Ti-Fe alloy, comprising the following steps:
[0036] The iron block and part of the copper block are smelted to obtain a Cu-Fe master alloy, which is then smelted with a titanium block and the remaining copper block to obtain an alloy ingot;
[0037] The alloy ingot is subjected to annealing treatment, hot extrusion, solution treatment, cold rolling deformation and aging treatment in sequence to obtain the high-strength and high-conductivity Cu-Ti-Fe alloy.
[0038] In a preferred embodiment, the mass ratio of the iron block to part of the copper block is 1:9.
[0039] In a preferred embodiment, the smelting is carried out under a protective atmosphere, the smelting temperature is 1050-1100°C, the time is 0.5-1h, and the pressure is 0.05MPa. If the temperature or time is higher than the above, it will cause the volatilization of key elements and abnormal coarseness of grains. If the temperature or time is lower than the above, the composition distribution will be uneven, affecting the alloy properties.
[0040] In a preferred embodiment, the annealing treatment is: heating the alloy ingot to 880°C and keeping the temperature for 40 minutes. If the temperature or time is higher than the above, the grains will grow abnormally, and if the temperature or time is lower than the above, the component segregation cannot be removed.
[0041] In a preferred embodiment, the hot extrusion is: keeping the temperature at 880°C for 40 minutes, and then hot extruding into a rod, with an extrusion ratio of 5 to 10:1. If the temperature or time is higher than the above, the structure will be coarsened, and if the temperature or time is lower than the above, the structure will be uneven. Moreover, it can only be obtained under the above extrusion ratio conditions.
[0042] In a preferred embodiment, the solution treatment is: keeping at 920°C for 1 hour and then quenching with water. If the temperature or time is higher than the above, the structure will be coarse, and if the temperature or time is lower than the above, the solute atoms will not be able to effectively dissolve into the matrix.
[0043] In a preferred embodiment, the cold rolling deformation is 60%. Only under this deformation condition can an alloy with excellent strength and electrical conductivity be obtained.
[0044] In a preferred embodiment, the aging treatment is performed at a temperature of 450-550° C. and for a time of 10-480 min.
[0045] More preferably, the aging temperature is 400°C, 450°C, 500°C and 550°C, and the aging time is 10 min, 20 min, 30 min, 60 min, 120 min, 240 min and 480 min. If the temperature or time is higher than the above, the alloy will recrystallize and the precipitation phase will coarsen. If the temperature or time is lower than the above, the precipitation strengthening effect will be weakened and the alloy performance will be reduced.
[0046] The embodiment of the present invention also discloses a high-strength and high-conductivity Cu-Ti-Fe alloy prepared by the above-mentioned preparation method.
[0047] In a preferred embodiment, the following components are included in mass fractions:
[0048] Ti: 1.3-1.6%, Fe: 0.5%, and the balance is Cu and inevitable impurities.
[0049] In a more preferred embodiment, the following components are included in mass fraction:
[0050] Ti: 1.5%, Fe: 0.5%, the balance is Cu and inevitable impurities.
[0051] Unless otherwise specified, the raw materials in the examples of the present invention were purchased from commercial sources;
[0052] The content of Ti in the titanium block is 99.99%;
[0053] The Fe content in the iron block is 99.99%;
[0054] The Cu content in copper block is 99.99%:
[0055] Unless otherwise specified, the room temperature or normal temperature in the embodiments of the present invention refers to 25±3°C.
[0056] Example 1
[0057] A method for preparing a high-strength and high-conductivity Cu-Ti-Fe alloy, such as Figure 1 As shown, the following steps are included:
[0058] (1) Weigh 0.075 kg of titanium block, 0.025 kg of iron block, and 4.9 kg of copper block, with a total mass of 5 kg. Then put the iron block and part of the copper block into a smelting furnace at a weight ratio of copper to iron = 9:1 for smelting. The pressure in the furnace is 5×10 2 Pa, then fill with argon until the pressure in the furnace is 0.05MPa, heat to 1080℃, smelt for 0.5-1h, and obtain Cu-10%Fe intermediate alloy after cooling for standby use.
[0059] (2) Melting, casting and peeling: In an argon atmosphere, the Cu-10% Fe master alloy, titanium block and the remaining copper block were heated at 1200°C and 6×10 -3 MPa is used for smelting to obtain an alloy melt, which is then poured into a sand mold, demoulded after cooling, and the riser is removed and the surface oxide scale is turned off to obtain an alloy ingot.
[0060] (3) heating the alloy ingot to 880° C., performing homogenization annealing for 40 min, then heating to 880° C. and keeping the temperature for 40 min, and then hot extruding into a rod with an extrusion ratio of 5 to 10:1 to obtain a rod blank;
[0061] (4) In a vacuum tube furnace, under the protection of argon, the above-mentioned rod blanks were solution treated at 920°C for 1 h. After the solution treatment, the alloy was taken out and water quenched, and then cold rolled with a deformation amount of 60%. Finally, the cold rolled alloy sample was aged at 450°C for 240 min to obtain a Cu-Ti-Fe alloy.
[0062] The TEM scanning electron microscope image is as follows Figure 2 As shown, it can be seen that a large amount of dispersed nanosized Fe2Ti phase is precipitated in the alloy.
[0063] Example 2
[0064] A method for preparing a high-strength and high-conductivity Cu-Ti-Fe alloy comprises the following steps:
[0065] (1) Weigh 0.075 kg of titanium block, 0.025 kg of iron block, and 4.9 kg of copper block, with a total mass of 5 kg. Then put the iron block and part of the copper block into a smelting furnace at a weight ratio of copper to iron = 9:1 for smelting. The pressure in the furnace is 5×10 2Pa, then fill with argon until the pressure in the furnace is 0.05MPa, heat to 1080℃, smelt for 0.5-1h, and obtain Cu-10%Fe intermediate alloy after cooling for standby use.
[0066] (2) Melting, casting and peeling: In an argon atmosphere, the Cu-10% Fe master alloy, titanium block and the remaining copper block were heated at 1200°C and 6×10 -3 MPa is used for smelting to obtain an alloy melt, which is then poured into a sand mold, demoulded after cooling, and the riser is removed and the surface oxide scale is turned off to obtain an alloy ingot.
[0067] (3) heating the alloy ingot to 880° C., performing homogenization annealing for 40 min, then heating to 880° C. and keeping the temperature for 40 min, and then hot extruding into a rod with an extrusion ratio of 5 to 10:1 to obtain a rod blank;
[0068] (4) In a vacuum tube furnace, under the protection of argon, the above-mentioned rod blanks were solution treated at 920°C for 1 h. After the solution treatment, the alloy was taken out and water quenched, and then cold rolled with a deformation amount of 60%. Finally, the cold rolled alloy sample was aged at 450°C for 120 min to obtain a Cu-Ti-Fe alloy.
[0069] Example 3
[0070] A method for preparing a high-strength and high-conductivity Cu-Ti-Fe alloy comprises the following steps:
[0071] (1) Weigh 0.075 kg of titanium block, 0.025 kg of iron block, and 4.9 kg of copper block, with a total mass of 5 kg. Then put the iron block and part of the copper block into a smelting furnace at a weight ratio of copper to iron = 9:1 for smelting. The pressure in the furnace is 5×10 2 Pa, then fill with argon until the pressure in the furnace is 0.05MPa, heat to 1080℃, smelt for 0.5-1h, and obtain Cu-10%Fe intermediate alloy after cooling for standby use.
[0072] (2) Melting, casting and peeling: In an argon atmosphere, the Cu-10% Fe master alloy, titanium block and the remaining copper block were heated at 1200°C and 6×10 -3 MPa is used for smelting to obtain an alloy melt, which is then poured into a sand mold, demoulded after cooling, and the riser is removed and the surface oxide scale is turned off to obtain an alloy ingot.
[0073] (3) heating the alloy ingot to 880° C., performing homogenization annealing for 40 min, then heating to 880° C. and keeping the temperature for 40 min, and then hot extruding into a rod with an extrusion ratio of 5 to 10:1 to obtain a rod blank;
[0074] (4) In a vacuum tube furnace, under the protection of argon, the above-mentioned rod blanks were solution treated at 920°C for 1 h. After the solution treatment, the alloy was taken out and water quenched, and then cold rolled with a deformation amount of 60%. Finally, the cold rolled alloy sample was aged at 450°C for 480 min to obtain a Cu-Ti-Fe alloy.
[0075] Example 4
[0076] A method for preparing a high-strength and high-conductivity Cu-Ti-Fe alloy comprises the following steps:
[0077] (1) Weigh 0.075 kg of titanium block, 0.025 kg of iron block, and 4.9 kg of copper block, with a total mass of 5 kg. Then put the iron block and part of the copper block into a smelting furnace at a weight ratio of copper to iron = 9:1 for smelting. The pressure in the furnace is 5×10 2 Pa, then fill with argon until the pressure in the furnace is 0.05MPa, heat to 1080℃, smelt for 0.5-1h, and obtain Cu-10%Fe intermediate alloy after cooling for standby use.
[0078] (2) Melting, casting and peeling: In an argon atmosphere, the Cu-10% Fe master alloy, titanium block and the remaining copper block were heated at 1200°C and 6×10 -3 MPa is used for smelting to obtain an alloy melt, which is then poured into a sand mold, demoulded after cooling, and the riser is removed and the surface oxide scale is turned off to obtain an alloy ingot.
[0079] (3) heating the alloy ingot to 880° C., performing homogenization annealing for 40 min, then heating to 880° C. and keeping the temperature for 40 min, and then hot extruding into a rod with an extrusion ratio of 5 to 10:1 to obtain a rod blank;
[0080] (4) In a vacuum tube furnace, under the protection of argon, the above-mentioned rod blanks were solution treated at 920°C for 1 h. After the solution treatment, the alloy was taken out and water quenched, and then cold rolled with a deformation amount of 60%. Finally, the cold rolled alloy sample was aged at 400°C for 240 min to obtain a Cu-Ti-Fe alloy.
[0081] Example 5
[0082] A method for preparing a high-strength and high-conductivity Cu-Ti-Fe alloy comprises the following steps:
[0083] (1) Weigh 0.075 kg of titanium block, 0.025 kg of iron block, and 4.9 kg of copper block, with a total mass of 5 kg. Then put the iron block and part of the copper block into a smelting furnace at a weight ratio of copper to iron = 9:1 for smelting. The pressure in the furnace is 5×10 2Pa, then fill with argon until the pressure in the furnace is 0.05MPa, heat to 1080℃, smelt for 0.5-1h, and obtain Cu-10%Fe intermediate alloy after cooling for standby use.
[0084] (2) Melting, casting and peeling: In an argon atmosphere, the Cu-10% Fe master alloy, titanium block and the remaining copper block were heated at 1200°C and 6×10 -3 MPa is used for smelting to obtain an alloy melt, which is then poured into a sand mold, demoulded after cooling, and the riser is removed and the surface oxide scale is turned off to obtain an alloy ingot.
[0085] (3) heating the alloy ingot to 880° C., performing homogenization annealing for 40 min, then heating to 880° C. and keeping the temperature for 40 min, and then hot extruding into a rod with an extrusion ratio of 5 to 10:1 to obtain a rod blank;
[0086] (4) In a vacuum tube furnace, under the protection of argon, the above-mentioned rod blanks were solution treated at 920°C for 1 h. After the solution treatment, the alloy was taken out and water quenched, and then cold rolled with a deformation amount of 60%. Finally, the cold rolled alloy sample was aged at 500°C for 240 min to obtain a Cu-Ti-Fe alloy.
[0087] Example 6
[0088] A method for preparing a high-strength and high-conductivity Cu-Ti-Fe alloy comprises the following steps:
[0089] (1) Weigh 0.075 kg of titanium block, 0.025 kg of iron block, and 4.9 kg of copper block, with a total mass of 5 kg. Then put the iron block and part of the copper block into a smelting furnace at a weight ratio of copper to iron = 9:1 for smelting. The pressure in the furnace is 5×10 2 Pa, then fill with argon until the pressure in the furnace is 0.05MPa, heat to 1080℃, smelt for 0.5-1h, and obtain Cu-10%Fe intermediate alloy after cooling for standby use.
[0090] (2) Melting, casting and peeling: In an argon atmosphere, the Cu-10% Fe master alloy, titanium block and the remaining copper block were heated at 1200°C and 6×10 -3 MPa is used for smelting to obtain an alloy melt, which is then poured into a sand mold, demoulded after cooling, and the riser is removed and the surface oxide scale is turned off to obtain an alloy ingot.
[0091] (3) heating the alloy ingot to 880° C., performing homogenization annealing for 40 min, then heating to 880° C. and keeping the temperature for 40 min, and then hot extruding into a rod with an extrusion ratio of 5 to 10:1 to obtain a rod blank;
[0092] (4) In a vacuum tube furnace, under the protection of argon, the above-mentioned rod blanks were solution treated at 920°C for 1 h. After the solution treatment, the alloy was taken out and water quenched, and then cold rolled with a deformation amount of 60%. Finally, the cold rolled alloy sample was aged at 500°C for 120 min to obtain a Cu-Ti-Fe alloy.
[0093] Comparative Example 1
[0094] A method for preparing a high-strength and high-conductivity Cu-Ti alloy is different from Example 1 in that Fe is not included in the raw material, and the Fe element is replaced by Cu. The remaining process steps and parameters are the same as those in Example 1.
[0095] Comparative Example 2
[0096] A method for preparing a high-strength and high-conductivity Cu-Ti-Fe alloy, which is different from Example 1 in that the raw materials include 0.075 kg of titanium block, 0.015 kg of iron block, and 4.91 kg of copper block, with a total mass of 5 kg. The remaining process steps and parameters are the same as those in Example 1.
[0097] Comparative Example 3
[0098] A method for preparing a high-strength and high-conductivity Cu-Ti-Fe alloy is different from Example 1 in that the cold rolling deformation is 40%. The remaining process steps and parameters are the same as those of Example 1.
[0099] Comparative Example 4
[0100] A method for preparing a high-strength and high-conductivity Cu-Ti-Fe alloy is different from Example 1 in that the cold rolling deformation is 80%. The remaining process steps and parameters are the same as those of Example 1.
[0101] Comparative Example 5
[0102] A method for preparing a high-strength and high-conductivity Cu-Ti-Fe alloy, which is different from Example 1 in that the aging treatment temperature is 600° C. and the aging time is 60 minutes. The remaining process steps and parameters are the same as those in Example 1.
[0103] Comparative Example 6
[0104] A method for preparing a high-strength and high-conductivity Cu-Ti-Fe alloy, which is different from that of Example 1 in that step (3) does not include hot extrusion. The remaining process steps and parameters are the same as those of Example 1.
[0105] Comparative Example 7
[0106] A method for preparing a high-strength and high-conductivity Cu-Ti-Fe alloy, which is different from that of Example 1 in that hot extrusion is first performed and then annealing is performed in step (3), specifically comprising the following steps:
[0107] (3) heating the alloy ingot to 880° C. and keeping the temperature for 40 min, and then hot-extruding it into a rod with an extrusion ratio of 5 to 10:1 to obtain a rod blank, and then heating it to 880° C. again and performing homogenization annealing for 40 min;
[0108] The remaining process steps and parameters are the same as those in Example 1.
[0109] Technical Effects
[0110] The hardness, conductivity and tensile strength of the alloys prepared in Examples 1 to 6 and Comparative Examples 1 to 5 were measured using a HVS-1000 Vickers hardness tester, a Singa 2008B1 digital conductivity meter and an AG-I-250 kN tensile machine. The results are shown in Table 1.
[0111] Table 1 Performance test results
[0112] Hardness / HV Electrical conductivity / %IACS Tensile strength / MPa Example 1 262 19.7 742.7 Example 2 245 17.8 716.9 Example 3 251 21.7 723.6 Example 4 237 15.7 697.2 Example 5 243 18.6 708.3 Example 6 259 18.1 723.7 Comparative Example 1 187 19.9 598.3 Comparative Example 2 256 18.7 735.6 Comparative Example 3 241 19.4 706.4 Comparative Example 4 253 17.4 724.1 Comparative Example 5 223 20.6 634.1 Comparative Example 6 239 16.7 684.7 Comparative Example 7 247 18.4 706.8
[0113] It can be seen from the test results in Table 1 that by adding Fe to the Cu-Ti alloy to form a Cu-Ti-Fe alloy, the microhardness and tensile strength of the alloy can be significantly improved, wherein the tensile strength is increased by 16.5% to 24.5%, while maintaining the good electrical conductivity of the alloy. The reason is that the Fe element in the alloy can produce solid solution strengthening, participate in the formation of the Fe2Ti phase, and promote the precipitation of the Cu4Ti phase. Comparative Example 1 and Comparative Example 1-2 show that the addition of the Fe element in the alloy and the increase in the Fe content significantly improve the microhardness and tensile strength of the alloy. Comparative Example 1 and Comparative Example 3 show that cold rolling deformation can produce work hardening and affect the alloy recrystallization process. Increasing the cold rolling deformation of the alloy can improve the microhardness and tensile strength of the alloy. In addition, with the extension of the aging time, the microhardness and tensile strength of the alloy show an increase first and then a decrease, while the electrical conductivity gradually increases. It has the best mechanical properties and electrical conductivity at 450°C for 240min, and the number of nano Cu4Ti and Fe2Ti phases precipitated in the alloy significantly affects the strength of the alloy. In summary, the present invention prepares a Cu-Ti-Fe alloy with high-strength electrical conductivity, solving the problem of low strength of Cu-Ti-Fe alloys.
[0114] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.
Claims
1. A method for preparing a high-strength and high-conductivity Cu-Ti-Fe alloy, characterized in that: The following steps are involved: The iron block and part of the copper block are smelted to obtain a Cu-Fe master alloy, which is then smelted with a titanium block and the remaining copper block to obtain an alloy ingot; The alloy ingot is subjected to annealing treatment, hot extrusion, solution treatment, cold rolling deformation and aging treatment in sequence to obtain the high-strength and high-conductivity Cu-Ti-Fe alloy.
2. The method for preparing a high-strength and high-conductivity Cu-Ti-Fe alloy according to claim 1, characterized in that: The mass ratio of the iron block to the portion of the copper block is 1:
9.
3. The method for preparing a high-strength and high-conductivity Cu-Ti-Fe alloy according to claim 1, characterized in that: The smelting is carried out under a protective atmosphere, the smelting temperature is 1050-1100° C., the time is 0.5-1 h, and the pressure is 0.05 MPa.
4. The method for preparing a high-strength and high-conductivity Cu-Ti-Fe alloy according to claim 1, characterized in that: The annealing treatment is as follows: heating the alloy ingot to 880° C. and keeping the temperature for 40 minutes.
5. The method for preparing a high-strength and high-conductivity Cu-Ti-Fe alloy according to claim 1, characterized in that: The hot extrusion is as follows: keeping the temperature at 880° C. for 40 minutes, and then hot extruding into rods, with an extrusion ratio of 5 to 10:
1.
6. The method for preparing a high-strength and high-conductivity Cu-Ti-Fe alloy according to claim 1, characterized in that: The solution treatment is: keeping the temperature at 920° C. for 1 hour and then quenching with water.
7. The method for preparing a high-strength and high-conductivity Cu-Ti-Fe alloy according to claim 1, characterized in that: The deformation amount of the cold rolling deformation is 60%.
8. The method for preparing a high-strength and high-conductivity Cu-Ti-Fe alloy according to claim 1, characterized in that: The temperature of the aging treatment is 450-550° C., and the time is 10-480 min.
9. A high-strength and high-conductivity Cu-Ti-Fe alloy prepared by the preparation method according to any one of claims 1 to 8.
10. A high-strength and high-conductivity Cu-Ti-Fe alloy according to claim 9, characterized in that: The following components are included in mass fraction: Ti: 1.3-1.6%, Fe: 0.5%, and the balance is Cu and inevitable impurities.
Citation Information
Cited By
Copper alloy, preparation method thereof and elastic electronic component
CN121700237A